2022
DOI: 10.5194/amt-15-1355-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spectral shape of continuous-wave lidar measurements in a turbulent wind tunnel

Abstract: Abstract. This paper describes the development of a theoretical model for the turbulence spectrum measured by a short-range, continuous-wave lidar (light detection and ranging). The lidar performance was assessed by measurements conducted with two WindScanners in an open-jet wind tunnel equipped with an active grid, for a range of different turbulent wind conditions. A hot-wire anemometer is used as reference to assess the lidar's measured statistics, time series and spectra. In addition to evaluating the stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Courtney et al (2008) reported instantaneous errors between co-located lidar probe volumes and cup anemometers to have standard deviation of 0.2 m/s and mean bias between -0.2 to 0.2 m/s, though they noted that the actual values depend on the distribution of wind speeds. A wind tunnel experiment by Van Dooren et al (2021) showed instantaneous velocity from a co-located lidar probe volume and hotwire anemometer with coefficients of determination much smaller than the 10-minute-averaged results above (i.e., 0.65 < 𝑅 2 < 0.95). As Pedersen and Courtney (2021), for instance, have shown that the standard error in line-of-sight velocity measured versus a hard target for a CW lidar is on the order of 0.1%, the main source of errors observed by Courtney et al 2021) is understood to be flow inhomogeneity and amplitude noise (neither of these cases included solid interference effects).…”
mentioning
confidence: 70%
“…Courtney et al (2008) reported instantaneous errors between co-located lidar probe volumes and cup anemometers to have standard deviation of 0.2 m/s and mean bias between -0.2 to 0.2 m/s, though they noted that the actual values depend on the distribution of wind speeds. A wind tunnel experiment by Van Dooren et al (2021) showed instantaneous velocity from a co-located lidar probe volume and hotwire anemometer with coefficients of determination much smaller than the 10-minute-averaged results above (i.e., 0.65 < 𝑅 2 < 0.95). As Pedersen and Courtney (2021), for instance, have shown that the standard error in line-of-sight velocity measured versus a hard target for a CW lidar is on the order of 0.1%, the main source of errors observed by Courtney et al 2021) is understood to be flow inhomogeneity and amplitude noise (neither of these cases included solid interference effects).…”
mentioning
confidence: 70%
“…1b), was used in staring mode with a sampling rate of 451.7 Hz. It has been previously used in the wind tunnel to model spectral shape of the lidar [11], to measure 2D velocity fields [3] and turbine wake deflection [10]. The measurement range of the WindScanner is between 20 m and 300 m [11].…”
Section: Measurement Configurationmentioning
confidence: 99%
“…It has been previously used in the wind tunnel to model spectral shape of the lidar [11], to measure 2D velocity fields [3] and turbine wake deflection [10]. The measurement range of the WindScanner is between 20 m and 300 m [11]. The probe volume of the WindScanner (l p ) is defined as the full width at half maximum of the Lorentzian intensity profile centered about its focus point and estimated using Equation 1.…”
Section: Measurement Configurationmentioning
confidence: 99%
“…Latter issue, however, can be addressed by tensor decompositions such as matrix product states. Further potential future applications include the small-scale enhancement of LIDAR measurements, where small-scale turbulent fluctuations are averaged over probe volumes [9,28], as well as the study of particle transport in the here-proposed synthetic fields. As far as basic turbulence research is concerned, the proposed joint multipoint statistics could also be applied to the hierarchical problem in a statistical description of the Navier-Stokes equation [55].…”
Section: Conclusion and Potential Model Improvementsmentioning
confidence: 99%
“…Second, we propose a method that constrains such random fields on sparse, point-wise atmospheric turbulence measurements; in our case propeller anemometers in a meteorological mast array. Our approach thus addresses the problem of incomplete measurements which arises for instance in laserbased Doppler anemometer measurements [27,28] or due to large surface areas covered by aerial measurements of the wakes of large wind park clusters [29]. It has to be stressed that although the present work discusses the reconstruction of a wind field in front of a wind turbine, our methodology is applicable to a broad range of problems in atmospherics physics and beyond.…”
Section: Introductionmentioning
confidence: 99%